Operations management in agriculture - Bochtis, Dionysis; Srensen, Claus Aage Grn; Kateris, Dimitrios (Academic Press is an imprint of Elsevier, 2019)
"Operations Management in Agriculture' bridges the knowledge gap on operations management for agricultural machinery. It complements traditional topics (cost of using and choosing machinery) with advanced engineering approaches recently applied in agricultural machinery management (area coverage planning and sequential scheduling). The book covers new technologies in bio-production systems (robotics, IoT) and environmental compliance by employing a systems engineering perspective with focuses on sub-systems, including advanced optimization, supply chain systems, sustainability, autonomous vehicles and IT-driven decision-making. It will be a valuable resource for students studying decision-making and those working to improve the efficiency, effectiveness and sustainability of production through machinery choice"--Publisher's description